STUDI PENGARUH PENAMBAHAN AL2O3 DAN SUHU SINTER TERHADAP KEKERASAN DAN BERAT JENIS RELATIF PADA ALUMINIUM SERBUK( AL MMC) - Rusianto, Toto (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2005)
Powder metallurgy is known as a method to produce aluminum metal matrix composites. The materials used in this research were Al alloy powder as the matrix and Al2O3 powder as the reinforcement. The Al alloy powder with irregular shape and particle size of 53 – 210 mm was produced by mechanical grinding method. Al2O3 powder with particle size 63 – 200 mm was supplied by Merck Germany. The various content of reinforcement were 0, 3, 6 and 9% weight of Al2O3. Each composition was compacted at pressures 500 MPa to produced green bodies. The green bodies were then sintered various temperatures were 450, 500, 550 and 600 oC for 2 hour in argon atmosphere. Density of specimens was measured using Archimedes method. Mechanical properties of the specimens used Vickers hardness. The results of the research show that relative density, increases with increasing temperature sintered. However relative density decreases with increasing of Al2O3 content. The optimum mechanical properties Vickers hardness were achieved on the composites containing 6% weight of Al2O3 with compacting pressure of 500 MPa and sintered temperature 550 oC. The investigation of micro structure showed amounts of porous was 9 to 20 percent, that relative density still low was 80 to 91 percent.